2013
DOI: 10.1155/2013/589641
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight to Bone Turnover: Role of ω‐3 Polyunsaturated Fatty Acids

Abstract: Background. Evidence has shown that long-chain polyunsaturated fatty acids (LCPUFA), especially the ω-3 fatty acids such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are beneficial for bone health and turnover. Objectives. This review summarizes findings from both in vivo and in vitro studies and the effects of LC PUFA on bone metabolism, as well as the relationship with the oxidative stress, the inflammatory process, and obesity. Results. Some studies in humans indicate that LCPUFA can increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 105 publications
1
55
1
4
Order By: Relevance
“…As most available drugs barely affect the level of AKP [13], it presented an obvious advantage of SIF over conventional agents. Consistent to our finding, Griel et al reported that omega‐3 fatty acids rich dietary oil efficiently down‐regulated AKP, interfered in bone metabolism and prevented bone resorption in vivo [14], which was due to regulations of some critical molecular signalings associated to cytokines production and calcium accretion [15]. However, we are not sure if similar mechanisms implicated in the effects of SIF on AA, because SIF was mainly composited by saturated and monounsaturated but not omega‐3 fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…As most available drugs barely affect the level of AKP [13], it presented an obvious advantage of SIF over conventional agents. Consistent to our finding, Griel et al reported that omega‐3 fatty acids rich dietary oil efficiently down‐regulated AKP, interfered in bone metabolism and prevented bone resorption in vivo [14], which was due to regulations of some critical molecular signalings associated to cytokines production and calcium accretion [15]. However, we are not sure if similar mechanisms implicated in the effects of SIF on AA, because SIF was mainly composited by saturated and monounsaturated but not omega‐3 fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…Perubahan ini berperan penting pada penurunan produksi IL-1, IL-6 dan TNF-alfa. 8 Konsumsi n-3 PUFA menurunkan TNF-alpha. Penurunan sitokin proinflamatori maupun eikosanoid oleh karena n-3 PUFA, menyebabkan konsumsi minyak ikan akan menyebabkan terjadinya peningkatkan pembentukan tulang, dan menurunkan destruksi tulang.…”
Section: Kata Kunci: Minyak Ikan Sardinella Longicep Osteoblas Apounclassified
“…oleh enzim-enzim lipoksigenase, siklooksigenase dan epoksigenase yang berasal dari n-6 PUFA. 8 Konsumsi n-3 PUFA, selama 2 minggu mengakibatkan peningkatan α-linolenic acid (ALA) sebanyak 3-4 × lipat, EPA 3 × lipat dan DHA 1,5 × lipat dalam membran sel. Peningkatan membran sel dengan n-3 PUFA tersebut menyebabkan penurunan produksi PGE2, tetapi akan meningkatkan PGE3 yang berfungsi sebagai anti inflamasi.…”
Section: Pembahasanunclassified
“…Kajarabille et al (2013) reported on largely bound fat intake and bone articular pathologies. Some studies on humans indicate that longchain poly unsaturated fatty acids (LCPUFA) can increase bone formation, affect peak bone mass in adolescents, and reduce bone loss (Kajarabille et al, 2013). The osteogenic potential of the nacre of mollusk shells is significantly documented (Atlan et al, 1997(Atlan et al, , 1999Lamghari et al, 1999;Lopez et al, 1992;Silve et al, 1992).…”
Section: Introductionmentioning
confidence: 99%